Arabic Speaking Class Student’s Perception Towards Oral Corrective Feedback - Azwir Azwir; Ahmad Arifin Bin Sapar; Zulkhairi Zulkhairi; Muhammad Yasir (Universitas Islam Negeri Palangka Raya Raya, 2026)
This study investigated university students' perceptions of oral corrective feedback (OCF) in Arabic speaking classes at State Islamic University Ar-Raniry, Banda Aceh. Employing a qualitative approach, semi-structured interviews were conducted with twelve purposively selected students from a cohort of seventy enrolled in Arabic speaking courses at an Islamic higher education institution in Indonesia. Data were analyzed using Braun and Clarke's (2006) thematic analysis framework. The findings revealed that students unanimously perceived OCF as essential for their Arabic speaking development. Explicit correction emerged as the most preferred feedback type, particularly among lower-achieving students, while high-achieving students favored clarification requests that promote self-repair. Students' affective responses were shaped primarily by the timing and manner of delivery, with post-performance and collective feedback strongly preferred over mid-performance correction, which triggered anxiety and embarrassment. OCF was perceived to improve phonological accuracy, morphosyntactic precision, self-monitoring capability, and speaking confidence. The study recommends that instructors diversify feedback strategies according to learners' proficiency levels and prioritize supportive, post-performance delivery to maximize pedagogical effectiveness.